1998
DOI: 10.2307/3579983
|View full text |Cite
|
Sign up to set email alerts
|

Chernobyl-Related Thyroid Cancer in Children of Belarus: A Case-Control Study

Abstract: The accident at the Chernobyl nuclear power plant on April 26, 1986, released approximately 2 EBq of 131I and other radioiodine isotopes that heavily contaminated southern Belarus. An increase in thyroid cancer reported in 1992 and attributed to the Chernobyl accident was challenged as possibly the result of intensive screening. We began a case-control study to test the hypothesis that the Chernobyl accident caused the increase in thyroid cancer. Records of childhood thyroid cancer in the national therapy cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(69 citation statements)
references
References 17 publications
2
65
0
2
Order By: Relevance
“…The most marked consequence of the exposure to radioiodine was a swift and pronounced increase in the incidence of childhood thyroid cancer in the most heavily contaminated areas of the former USSR, the number of excess cases being approximately 2000 to date (UNSCEAR, 2000;Williams, 2002). There is a strong relationship between childhood thyroid cancer and the estimated dose from radioiodine (Astakhova et al, 1998;UNSCEAR, 2000). Evidence for an increase in thyroid cancer among those exposed as adults is much less clear (Ivanov et al, 2003), but the notable sensitivity of the thyroid of children to radiation-induced cancer is apparent in studies of those exposed to external sources of radiation (Ron et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The most marked consequence of the exposure to radioiodine was a swift and pronounced increase in the incidence of childhood thyroid cancer in the most heavily contaminated areas of the former USSR, the number of excess cases being approximately 2000 to date (UNSCEAR, 2000;Williams, 2002). There is a strong relationship between childhood thyroid cancer and the estimated dose from radioiodine (Astakhova et al, 1998;UNSCEAR, 2000). Evidence for an increase in thyroid cancer among those exposed as adults is much less clear (Ivanov et al, 2003), but the notable sensitivity of the thyroid of children to radiation-induced cancer is apparent in studies of those exposed to external sources of radiation (Ron et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…As part of their normal, day-to-day operations, NPPs emit low levels of ionizing radiation that may pose health risks to those living in proximity and subject to prolonged exposure (Blevins and Andersen 2011). In general, the ionizing radiation emitted from NPPs has been linked to various forms of cancer, permanent damage to human vital organs, and death (Astakhova et al 1998;Cardis et al 2005;Canu et al 2008;Anzai et al 2012). The Fukushima NPP began to release significant excess radiation into the atmosphere the day after the accident (Thakur et al 2013;Baba 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are only four published population-based case-control studies of thyroid cancer in children. One, based on 107 cases diagnosed in Belarus, found a strong relationship between estimated radiation dose and thyroid cancer, but thyroid doses were inferred for children from estimates for adults who lived in the same villages (16). Two studies, based on a total of 66 cases and individual estimates of thyroid radiation dose, found that the risk of thyroid cancer was significantly increased in a dose-dependent manner among residents of Bryansk Oblast of the Russian Federation who were exposed as children and adolescents to radiation fallout from the Chernobyl accident (17,18).…”
Section: Introductionmentioning
confidence: 99%